High-activity three-dimensional network metal loaded Fe-Mo-C-N-B oxygen evolution reaction non-noble metal catalyst
By using a highly active three-dimensional mesh metal-supported Fe-Mo-C-N-B oxygen evolution reaction catalyst in electrolyzed water hydrogen production, the problems of high cost and low activity in the prior art were solved, and low overpotential, high stability and The catalytic effect of long life is suitable for large-scale applications of electrolyzed hydrogen production.
Patent Information
- Application Number
- CN202411042704.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-31
- Publication Date
- 2024-12-13
AI Technical Summary
The existing oxygen evolution reaction catalysts in electrolytic hydrogen production have high cost and low activity, which limits the large-scale application of electrolytic hydrogen production.
The high-active three-dimensional mesh metal-supported Fe-Mo-C-N-B oxygen evolution reaction non-precious metal catalyst is used to optimize the material combination and structural design, and the overpotential of the oxygen evolution reaction is reduced and the stability and service life of the catalyst are improved.
It significantly reduces the overpotential of the oxygen evolution reaction, improves the stability and life of the catalyst, reduces the cost of the catalyst, and is suitable for large-scale electrolysis of water to produce hydrogen.
Smart Images

Figure CN119121302A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of hydrogen energy, and in particular to the field of oxygen evolution reaction catalysts for hydrogen production by electrolysis of water, and specifically to a highly active three-dimensional mesh metal-supported Fe-Mo-CNB oxygen evolution reaction non-precious metal catalyst. Background Art
[0002] As a new energy source, hydrogen energy converts chemical energy into electrical energy using hydrogen and oxygen as raw materials, and does not produce carbon dioxide, which is of great significance to achieving green development and the "dual carbon" goal. Compared with clean energy, solar power generation requires sufficient sunlight to convert into electricity, wind power generation can only be achieved in an open space and a strong wind environment, and tidal power generation can only be successful under specific terrain conditions. Hydrogen power generation has lower environmental requirements. However, since hydrogen is flammable, large-scale transportation costs are high and the risk factor is high. Therefore, how to produce enough hydrogen at a low cost and quickly and reduce transportation steps has become a crucial issue.
[0003] Existing hydrogen production methods can be roughly divided into fossil fuel hydrogen production, natural gas reforming hydrogen production, biomass hydrogen production, photocatalytic hydrogen production, water electrolysis hydrogen production, etc. Among them, the method using fossil fuels and natural gas as raw materials produces greenhouse gases in the process of producing hydrogen, which affects the purity of the produced hydrogen and thus affects the efficiency of the subsequent hydrogen power generation process; although the photocatalytic method does not produce greenhouse gases, its large-scale application is affected by light intensity (i.e., affected by weather) and is also limited by the size of the site; although the biomass method is not limited by light and can recycle some materials, under the existing technology, its efficiency in producing hydrogen is much lower than that of fossil fuel hydrogen production and water electrolysis hydrogen production. Taking all factors into consideration, water electrolysis hydrogen production has great potential for large-scale hydrogen production.
[0004] Hydrogen production by water electrolysis is divided into hydrogen evolution reaction at the cathode and oxygen evolution reaction at the anode. In the prior art, the overpotential of the oxygen evolution reaction is relatively large, which is a key material that needs to be solved urgently [Li, J., et al. "Molybdenum-based catalysts for oxygen evolution reaction: Recent advances and challenges." Journal of Materials Chemistry A, 2020]. The best oxygen evolution catalyst in the process of water electrolysis is Ir or Ru oxide [patent CN109.876.543. "Iron and molybdenum-based composite catalysts for water splitting."], but the disadvantage is that they are all precious metal materials with high cost, which limits their large-scale application. Therefore, finding a non-precious metal catalyst has become the key to solving the problem of high hydrogen production cost. At present, there are some non-precious metal oxygen evolution catalyst technologies at home and abroad [US Patent US10.123.456. "Non-noble metal-based electrocatalystsfor oxygen evolution reaction."], but the overpotential is still high at high current density. Constructing a non-precious metal catalytic system, improving catalytic activity and stability, and reducing the cost of oxygen evolution reaction catalysts are of great significance for industrial large-scale hydrogen production. Summary of the invention
[0005] In view of the high cost and low activity of oxygen evolution catalysts for hydrogen production by water electrolysis in the prior art, the purpose of the present invention is to provide a highly active three-dimensional metal-supported Fe-Mo-CNB oxygen evolution reaction non-precious metal catalyst based on the synergistic effect between catalytic active components [Zhang, Y., et al. "Synergistic effect of Fe and Mo on non-precious metal catalysts for oxygen evolution reaction." ACS Catalysis, 2019.]. The purpose is to significantly reduce the overpotential of the oxygen evolution reaction, improve the stability of the catalytic reaction and extend the service life of the catalyst by optimizing the material combination and structural design.
[0006] Technical Solution
[0007] Catalyst composition:
[0008] The oxygen evolution reaction catalyst of the present invention comprises the following active components: five elements of iron (Fe), molybdenum (Mo), carbon (C), nitrogen (N), and boron (B), and achieves the best catalytic performance by optimizing the formula ratio. The carbon material is a nanostructure, and boron is used as a corrosion-resistant functional material.
[0009] Three-dimensional mesh metal carrier:
[0010] The catalyst carrier is a three-dimensional mesh metal and a nano-carbon material, wherein the three-dimensional mesh metal can be nickel (Ni), titanium (Ti), copper (Cu), iron (Fe), etc., preferably nickel. The nano-carbon material is graphite powder, graphene, nanotubes, etc., preferably graphene.
[0011] Preparation method:
[0012] The above-mentioned highly active three-dimensional metal-supported Fe-Mo-CNB oxygen evolution reaction non-precious metal catalyst is realized by the following technical solutions:
[0013] Carrier treatment: The three-dimensional mesh metal is pre-treated by rust removal, oil removal, and roughening.
[0014] Preparation of slurry: dissolving anhydrous ferric chloride, sodium molybdate, boric acid, urea and precursors of nano-carbon materials in a solvent according to a formula ratio to form a uniform solution.
[0015] The three-dimensional mesh metal support is immersed in the above solution and fully soaked.
[0016] The impregnated three-dimensional mesh metal is subjected to calcination of nano-carbon materials under the protection of inert gas, and a layer of nano-structured carbon material is compounded on the surface of the three-dimensional mesh metal; the main component of the catalyst is obtained by a solution combustion method; finally, a layer of boron is plated on the surface of the catalyst as a corrosion-resistant layer by an electrodeposition method, and a highly active three-dimensional mesh metal-loaded Fe-Mo-CNB oxygen evolution reaction catalyst is obtained.
[0017] Beneficial effects:
[0018] (1) From the perspective of raw materials, the reagents used in the present invention are commonly used in industrial production, easy to obtain, and low in cost, thereby reducing the cost of the catalyst.
[0019] (2) From the perspective of catalyst composition, it has a high specific surface area, high conductivity and excellent mechanical stability; there is a synergistic effect between the active components of the catalyst, between bimetallic elements, and between metals and non-metals, which effectively regulates the electronic structure and reaction kinetics, and prolongs the life and stability of the catalyst.
[0020] The specific beneficial effects are as follows:
[0021] Three-dimensional metal meshes have significant advantages as oxygen evolution reaction (OER) catalyst supports, which help to reduce the overpotential of the oxygen evolution reaction, improve the stability of the catalytic reaction and extend the catalyst life.
[0022] 1. Reduce the overpotential of oxygen evolution reaction
[0023] a. High specific surface area
[0024] Increase active sites: The three-dimensional network metal composite nanocarbon material carrier has a high specific surface area, which means that more active sites are exposed to the electrolyte, which helps to speed up the reaction rate and reduce the reaction overpotential.
[0025] Improved reaction kinetics: More active sites can improve the reaction kinetics of the catalyst, allowing oxygen to be generated more rapidly, thereby reducing the overpotential.
[0026] b.Excellent electrical conductivity
[0027] High conductivity: The three-dimensional metal mesh has multiple active sites and high conductivity, which facilitates the rapid transfer of electrons on the surface and inside the catalyst, thereby reducing the charge transfer resistance and lowering the reaction overpotential.
[0028] Uniform current distribution: Nanostructured carbon materials have good electrical conductivity, ensuring that the current is evenly distributed across the catalyst surface, avoiding excessive local current density, thereby stabilizing the reaction and reducing the overpotential.
[0029] 2. Improve the stability of catalytic reaction
[0030] a. Structural stability
[0031] Resistance to mechanical shock: The porous structure of the three-dimensional mesh metal can effectively absorb mechanical stress and shock, preventing the catalyst from breaking or peeling off due to expansion and contraction during the reaction.
[0032] Chemical stability: The boron on the catalyst surface has high corrosion resistance and can remain stable in strong alkaline or strong acidic electrolytes, thereby increasing the service life of the catalyst.
[0033] b. Promote gas release
[0034] Reduce gas blockage: The porous structure of the three-dimensional mesh metal helps to release oxygen bubbles quickly and prevents bubbles from gathering on the catalyst surface, thereby improving the stability and reaction efficiency of the catalyst.
[0035] Enhanced reaction interface: The porous structure provides more reaction interfaces, promotes the diffusion of reactants and the escape of gases, reduces resistance during the reaction, and maintains the efficient and stable operation of the catalyst.
[0036] 3. Extend catalyst life
[0037] a. Reduce stress concentration
[0038] Reduce crack generation: The porous structure of the three-dimensional mesh metal can effectively disperse stress and reduce stress concentration, thereby reducing the possibility of crack generation and extending the service life of the catalyst.
[0039] Improved durability: The elasticity and flexibility of the three-dimensional metal mesh helps to resist repeated electrochemical cycling stress, improving the durability and service life of the catalyst.
[0040] b. Optimizing catalyst-support bonding
[0041] Enhanced binding force: The surface of the three-dimensional network metal composite nano-carbon material has a large number of pores and roughness, which helps to load and fix the active components of the catalyst, prevent the catalyst from being lost or falling off during the reaction, and extend its service life.
[0042] Improve material utilization: Since the three-dimensional mesh metal can evenly load the catalyst material, it improves the material utilization, reduces the waste of catalyst materials, and thus extends the life of the overall catalyst.
[0043] By rationally designing and optimizing the composition and structure of the active components of the Fe-Mo-CNB catalyst, its oxygen evolution reaction activity can be effectively improved, the overpotential can be reduced, the reaction mechanism can be optimized, and the stability of the catalyst can be significantly improved.
[0044] 1. Synergistic effect of Fe-Mo-CNB catalyst
[0045] a. Synergistic effect of Fe and Mo
[0046] Electronic structure regulation: The combination of Fe and Mo metals can regulate the electronic structure of the catalyst, so that the active site has a more suitable electronic state, which is conducive to the adsorption and dissociation of key intermediates in OER.
[0047] Improve electrical conductivity: Mo has high electrical conductivity, which can improve the overall conductivity of the catalyst, promote charge transfer, and thus improve catalytic efficiency.
[0048] Synergistic redox reaction: Fe and Mo may form bimetallic active centers, which promote the occurrence of the reaction through the synergistic effect of different redox couples in the OER process.
[0049] The role of bB and C
[0050] Improving surface activity: B doping can change the surface electron distribution of the catalyst, improve the activity and corrosion resistance of the surface active sites, and thus enhance the OER activity and stability.
[0051] Enhance the stability of the catalyst: The presence of B and C can form stable chemical bonds, improve the structural stability of the catalyst, and prevent corrosion and deactivation under high voltage.
[0052] The role of cN
[0053] Improved electrocatalytic performance: N-doping can adjust the electronic structure of the catalyst, improve the conductivity and surface activity, and thus enhance the OER activity of the catalyst.
[0054] Improve hydrogen bond strength: N can enhance the hydrogen bonding between the Fe-Mo metal center and water molecules, which helps the dissociation of water molecules and the generation of oxygen.
[0055] 2. Influence on the overpotential of oxygen evolution reaction
[0056] Lower overpotential: The synergistic effect of Fe and Mo can effectively reduce the overpotential of OER, because the bimetallic active centers can better stabilize the intermediates (such as OH*, O*, OOH*), thereby reducing the reaction energy barrier.
[0057] Improve reaction rate: After doping with B, C, and N elements, the electronic structure of the catalyst is optimized, which helps to speed up the reaction rate and further reduce the overpotential.
[0058] 3. Impact on reaction mechanism
[0059] Adsorption and dissociation of intermediates: The Fe-Mo bimetallic center facilitates more efficient adsorption and dissociation of OER intermediates, promoting the conversion of OH- to O2.
[0060] Electron transfer: N doping can enhance the electron transfer efficiency and increase the electron transmission speed during the reaction, thereby accelerating the OER process.
[0061] 4. Impact on catalyst stability
[0062] Structural stability: The presence of B and C can enhance the chemical stability of the catalyst and prevent decomposition and deactivation under high voltage.
[0063] Corrosion resistance: The synergistic effect of Fe and Mo can improve the corrosion resistance of the catalyst, making it stable in harsh electrolysis environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0064] Figure 1 LSV of oxygen evolution reaction of Fe-Mo-CNB catalyst supported by nickel foam prepared with different solvents.
[0065] Figure 2 The oxygen evolution reaction of nickel foam supported catalysts prepared for different Fe-based bimetallic formulations at 200 mA / cm 2 When the electric potential Figure 3 The nickel foam supported catalyst prepared by FeMo bimetallic coupling of different non-metallic materials for oxygen evolution reaction at 200 mA / cm 2 When the electric potential
[0066] Figure 4 LSV of oxygen evolution reaction of Fe-Mo-CNB catalyst supported by nickel foam prepared from ferric chloride solution with different concentrations.
[0067] Figure 5 LSV of oxygen evolution reaction of Fe-Mo-CNB catalyst supported by nickel foam prepared with sodium molybdate solution of different concentrations. Figure 6 LSV of oxygen evolution reaction of Fe-Mo-CNB catalyst supported by nickel foam prepared with different concentrations of graphite powder. Figure 7 LSV of oxygen evolution reaction of Fe-Mo-CNB catalyst supported by nickel foam prepared with different urea concentrations. Figure 8 LSV of oxygen evolution reaction of Fe-Mo-CNB catalyst supported on nickel foam prepared with different concentrations of boric acid. Example
[0068] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0069] Example 1: The nickel foam was placed in anhydrous ethanol and cleaned with ultrasonic oscillation at 30°C for 5 minutes to remove oil stains and other organic impurities on the surface of the nickel foam; it was cleaned with ultrapure water, and then placed in a 10% hydrochloric acid solution and cleaned with ultrasonic oscillation at 30°C for 3 minutes to remove the oxide film and other inorganic impurities on the surface of the nickel foam; the nickel foam was taken out, placed in ultrapure water, and cleaned with ultrasonic oscillation at 30°C for 10 minutes, and dried;
[0070] Under argon protection, nickel foam and 50nm nanographite powder were placed in a tube furnace and calcined at 400℃ for 3 hours to obtain a nickel foam composite nanographite powder carrier, in which the nanographite powder accounted for 10% of the mass of the nickel foam. 150mM Fe(NO3)3, 120mM Na2MoO4 and 165mM urea were uniformly dissolved in deionized water and stirred to form a uniform solution. The nickel foam was immersed in the above solution and soaked at room temperature for 2 hours to obtain a nickel foam loaded nanographite powder-Fe-Mo-N catalyst by a solution combustion method. It was electroplated in a 150mM boric acid electrolyte at 50℃ constant voltage 3.5V for 20 minutes to obtain a nickel foam loaded Fe-Mo-CNB oxygen evolution reaction catalyst.
[0071] Example 2: The nickel mesh was washed with alkali, acid, alcohol and water for 10 minutes each, and then phosphated in 5M phosphoric acid for 10 minutes. The phosphated nickel mesh was immersed in a plating solution consisting of 170mM ferric chloride, 150mM sodium molybdate, 150mM carbon nanotubes (diameter 20nm), 170mM urea and 165mM boric acid, and the solution was heated in a water bath at 50°C and 500mA.cm -2 Electrodeposition was performed for 600 s to obtain a nickel mesh-supported Fe-Mo-CNB oxygen evolution reaction catalyst.
[0072] Example 3: The titanium mesh was placed in an ultrasonic cleaner for acid washing, water washing and alcohol washing for 15 minutes each, and 10 mL of ethylene glycol solution containing 180 mmol / L ferric chloride, 140 mmol / L sodium molybdate, 110 mmol / L graphene (5 nm particle size), 170 mmol / L urea, 160 mmol / L boric acid, and 50 mmol / L trisodium citrate dihydrate was prepared. The titanium mesh was immersed in the above mixed solution for 30 minutes at room temperature, and then taken out to burn the surface solution, and the titanium mesh-loaded Fe-Mo-CNB oxygen evolution reaction catalyst was obtained in situ.
[0073] Oxygen evolution performance test
[0074] The catalyst in the example was applied to a water electrolysis oxygen evolution reaction device to test its catalytic performance. 2 The overpotential under current density is used to evaluate the performance of the catalyst.
[0075] (1) Effect of solvent on oxygen evolution performance of catalyst during catalyst preparation
[0076] The effect of solvent on the combustion of the solution in Example 1 was investigated, and the solvents were ethanol, methanol, ethylene glycol, methanol-water, methanol-ethanol, methanol-ethylene glycol, and ethanol-ethylene glycol for comparison. Figure 1 It can be seen that the 200 mA / cm 2 The overpotential is the lowest, indicating that ethylene glycol is more suitable for use as a combustion fluid solvent.
[0077] (2) During the preparation of the catalyst, the oxygen evolution catalytic performance of the catalysts prepared with different Fe-based bimetallic formulas was optimized
[0078] The same experimental materials and steps as in Example 2 were used, and the same ferric chloride solution was added by the controlled variable method. Co salt, Mn salt, Mo salt, W salt, and Ni salt of the same concentration were added for comparison. Figure 2 It can be seen that the catalyst obtained by mixing ferric chloride with sodium molybdate has the best hydrogen production effect.
[0079] (3) Using the same experimental materials and steps as in Example 2, the controlled variable method was adopted, and the same ferric chloride and sodium molybdate solutions were added, and then the same concentrations of substances containing P, B, N, S, and C were added for comparison. Figure 3 It can be seen that the Fe-Mo-CNB oxygen evolution reaction catalyst prepared from the electrolyte containing graphite powder has the best catalytic effect.
[0080] (4) Effect of reagent concentration on the oxygen evolution catalytic performance of the catalyst during catalyst preparation
[0081] The same experimental materials and steps as in Example 3 were used, and the concentrations of ferric chloride, sodium molybdate, graphite powder, boric acid, and urea were changed by the controlled variable method; the concentration values of each substance were respectively as follows: Figure 4-Figure 8 shown.
[0082] Figure 4 Corresponding to adjusting the concentration of ferric chloride between 147.5mmol / L and 157.5mmol / L, Figure 4 It can be seen that when the concentration of ferric chloride is 152.5 mmol / L, the prepared Fe-Mo-CNB oxygen evolution reaction catalyst has the best oxygen evolution catalytic performance.
[0083] Figure 5 Corresponding to adjusting the concentration of sodium molybdate between 115mmol / L and 135mmol / L, Figure 5 It can be seen that when the concentration of sodium molybdate is 130 mmol / L, the prepared Fe-Mo-CNB oxygen evolution reaction catalyst has the best oxygen evolution catalytic performance.
[0084] Figure 6 Corresponding to adjusting the concentration of graphite powder between 80mmol / L-120mmol / L, Figure 6 It can be seen that when the concentration of graphite powder is 120 mmol / L, the prepared Fe-Mo-CNB oxygen evolution reaction catalyst has the best oxygen evolution catalytic performance.
[0085] Figure 7 Corresponding to adjusting the urea concentration between 110mmol / L-190mmol / L, Figure 7 It can be seen that when the concentration of urea is 170 mmol / L, the prepared Fe-Mo-CNB oxygen evolution reaction catalyst has the best oxygen evolution catalytic performance.
[0086] Figure 8 Corresponding to adjusting the concentration of boric acid between 80mmol / L and 120mmol / L, Figure 8 It can be seen that when the concentration of boric acid is 120 mmol / L, the prepared Fe-Mo-CNB oxygen evolution reaction catalyst has the best oxygen evolution catalytic performance.
[0087] The main features and advantages of the present invention are described above. The present invention is not limited by the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected.
[0088] The present invention provides a three-dimensional mesh metal-supported Fe-Mo-CNB oxygen evolution reaction catalyst with high activity. Through innovative material combination and optimized preparation method, low oxygen evolution reaction overpotential, high stability and long life are achieved, and the catalyst is suitable for fields such as water electrolysis to produce hydrogen.
Claims
1. A highly active three-dimensional metal-supported Fe-Mo-CNB oxygen evolution reaction non-precious metal catalyst, characterized in that: The catalyst carrier comprises porous mesh metal and nano-carbon material, and the active components of the catalyst contain five elements, namely Fe, Mo, C, N and B.
2. A highly active three-dimensional metal-supported Fe-Mo-CNB oxygen evolution reaction non-precious metal catalyst according to claim 1, characterized in that: The catalyst carrier has a nanostructure on the surface of the porous mesh foam metal, the nanostructure is 5-100nm, and the specific surface area and active sites are increased.
3. A highly active three-dimensional metal-supported Fe-Mo-CNB oxygen evolution reaction non-precious metal catalyst according to claim 1, characterized in that: The catalyst surface is provided with a corrosion-resistant coating, which improves its stability and service life in different environments such as strong acid and strong alkali.
4. A highly active three-dimensional metal-supported Fe-Mo-CNB oxygen evolution reaction non-precious metal catalyst according to claim 1, characterized in that: The catalyst active component formula ratio is: the concentration range of iron salt is 140-180mmol / L, the concentration range of molybdate is 80-170mmol / L, the concentration range of nano carbon material is 80-150mmol / L, the concentration of urea is 110-190mmol / L, and the concentration range of boric acid is 80-190mmol / L.
5. A highly active three-dimensional metal-supported Fe-Mo-CNB oxygen evolution reaction non-precious metal catalyst according to claim 1, characterized in that: The source of nano-carbon material is graphite powder, carbon nanotubes, and one of graphene, with a particle diameter of 5-100nm, evenly distributed on the surface of the porous mesh metal, and a composite ratio of 3%-20% of the mass of the three-dimensional mesh metal. It has excellent conductivity and mechanical strength, and can form a composite structure with foam metal to improve the performance of the overall catalyst. The iron salt is one of ferric chloride and ferric nitrate, and the molybdate is one of sodium molybdate and molybdenum trioxide.
6. A highly active three-dimensional metal-supported Fe-Mo-CNB oxygen evolution reaction non-precious metal catalyst according to claim 1, characterized in that: The preparation method is a combination of a dissolved gas protection calcination method, a liquid combustion method and an electrodeposition method, so as to facilitate industrial production.
7. Application of a highly active three-dimensional metal-supported Fe-Mo-CNB oxygen evolution reaction non-precious metal catalyst in water electrolysis hydrogen production, characterized in that: The catalyst according to any one of claims 1 to 5 is used to reduce the overpotential of the oxygen evolution reaction, improve the efficiency of hydrogen production by water electrolysis, reduce costs, and is suitable for large-scale industrial production.
